Effect of genetic variation in UGT1A and ABCB1 on moxifloxacin pharmacokinetics in South African patients with tuberculosis. (January 2018) - Naidoo, Anushka; Ramsuran, Veron; Chirehwa, Maxwell; Denti, Paolo; McIlleron, Helen; Naidoo, Kogieleum; Yende-Zuma, Nonhlanhla; Singh, Ravesh; Ngcapu, Sinaye; Chaudhry, Mamoonah; Pepper, Michael S; Padayatchi, Nesri
Aim: We assessed the effect of genetic variability in UGT1A and ABCB1 genes on moxifloxacin pharmacokinetics.Methods: Genotypes for selected UGT1A and ABCB1 SNPs were determined using a TaqMan ® Genotyping OpenArray ™ and high-resolution melt analysis for rs8175347. A nonlinear mixed-effects model was used to describe moxifloxacin pharmacokinetics.Results: Genotypes of UGT1A SNPs, rs8175347 and rs3755319 (20.6% lower and 11.6% increased clearance, respectively) and ABCB1 SNP rs2032582 (40% reduced bioavailability in one individual) were significantly associated with changes in moxifloxacin pharmacokinetic parameters.Conclusion: Genetic variation in UGT1A as represented by rs8175347 to a lesser extent rs3755319 and the ABCB1 rs2032582 SNP is modestly associated with the interindividual variability reported in moxifloxacin pharmacokinetics and exposure. Clinical relevance of the effects of genetic variation on moxifloxacin pharmacokinetic requires further investigation.